THE INFLUENCE OF INTELLECTUAL CAPITAL ON COMPANY VALUE WITH CORPORATE GOVERNANCE AS A MEDIATION VARIABLE - Ana Mardiana; Paulus Tangke; Angel Excella Virghita (SIMAK, 2022)
The purpose of this study is to investigate the effect of intellectual capital on firm value mediated by corporate governance. The variables used in this study are intellectual capital as an independent variable, company value as the dependent variable, and corporate governance as a mediating variable. The population used is all mining companies listed on the Indonesia Stock Exchange (IDX) with the study period in 2016-2018. The number of samples is 31 companies each year, selected by the purposive sampling method. This study uses documentary data, namely annual reports and financial reports. Path analysis is used to analyze data with the test equipment used, namely the classic assumption test, hypothesis test and sobel test. The method used in data collection is non-participant observation, by making observations, taking notes, and studying the annual reports and financial statements of companies that are published by the IDX. The results of this study indicate that corporate governance is unable to mediate the relationship between intellectual capital and firm value. Where intellectual capital has a significant negative effect on corporate governance, intellectual capital does not have a significant positive effect on firm value, and corporate governance has a significant positive effect on firm value.